Ali je merjenje kakovosti življenja ustrezen kazalnik učinkovitosti zaposlitvene rehabilitacije? - Bandel, Teja (Rehabilitacija (Ljubljana), 2015)
Background: The Centre for Vocational Rehabilitation in Ljubljana, which operates within the University Rehabilitation Institute, is participating in the European Platform for Rehabilitation as a member of the group for benchmarking in the field of outcome assessment in vocational rehabilitation (VR). Within the group, the QOLIS questionnaire (Quality of Life Impact of Vocational Rehabilitation Services) was developed for assessing three dimensions of quality of life, namely personal development, social inclusion and well-being. Methods: QOLIS was administered to the participants at the time of terminating a programme of VR. Apart from 55 items related to change in quality of life, the demographic data is requested containing information about gender, age, education, type of disability, life circumstances, VR duration and outcome. The data for the analysis derive from a sample of 103 persons. The data were statistically analysed with Excel and SPSS programs estimating means and statistically significant differences between groups (t-test, ANOVA). Results: The majority of the participants reported on experiencing improvement in their quality of life after completing the VR programme. Statistically significant differences in quality of life were found between participant groups differing in educational levels, VR outcome, programme location (Ljubljana or Maribor), and life circumstances. No statistically significant differences were found between men and women, groups of different age, or with respect to type of disability, year of programme completion and VR duration. Conlusions: The findings of the study speak in favour of the usefulness of the QOLIS for outcome assessment in VR programmes. The results of the study and further use of the questionnaire can provide useful information for improving existing vocational rehabilitation programmes in terms of leading to better quality of life.
Keywords: Employment; kakovost življenja; ocenjevanje izida; Outcome Assessment; Quality of Life; rehabilitacija; standard of living; vocational rehabilitation; zaposlovanje